39‐3: Invited Paper: LTPO TFT Technology for AMOLEDs†. Issue 1 (29th May 2019) - Chang, Ting-Kuo; Lin, Chin-Wei; Chang, Shihchang
Abstract : Low‐temperature Poly‐Crystalline Silicon and Oxide (LTPO) Thin‐Film Transistor (TFT) is introduced and developed as a TFT backplane of the AMOLED display for the first time in Apple Watch Series 4. With new panel circuitry and complementary driving scheme, the LTPO AMOLED display can be operated at a low refresh rate without any visible artifact.